Research seminar in the context of designing and preparing a master’s thesis - Palchyk, Henadzi V.; Prakharenko, Olesya G. (University Pedagogical Journal, 2024)
The content and potential of the research seminar «Designing and preparing a master’s thesis», which is included in the educational component of the curriculum for students receiving advanced higher education, are described. The sections of this seminar are presented. The specifics of the organisation of the educational process in the context of designing and preparing a master’s thesis are considered.
Keywords: advanced higher education; master’s degree; research activities of students